Effectiveness of COVID-19 vaccination in healthcare workers in Shiga Prefecture, Japan - Chano, Tokuhiro; Yamashita, Tomoko; Fujimura, Hirokazu; Kita, Hiroko; Ikemoto, Toshiyuki; Kume, Shinji; Morita, Shin-ya; Suzuki, Tomoyuki; Kakuno, Fumihiko (Scientific reports, 2022)
This study, which included serological and cellular immunity tests, evaluated whether coronavirus disease 2019 (COVID-19) vaccination adequately protected healthcare workers (HCWs) from COVID-19. Serological investigations were conducted among 1600 HCWs (mean ± standard deviation, 7.4 ± 1.4 months after the last COVID-19 vaccination). Anti-SARS-CoV-2 antibodies N-Ig, Spike-Ig (Roche), N-IgG, Spike-IgM, and -IgG (Abbott), were evaluated using a questionnaire of health condition. 161 HCWs were analyzed for cellular immunity using T-SPOT ® SARS-CoV-2 kit before, and 52 HCWs were followed up until 138.3 ± 15.7 days after their third vaccination. Spike-IgG value was 954.4 ± 2282.6 AU/mL. Forty-nine of the 1600 HCWs (3.06%) had pre-existing SARS-CoV-2 infection. None of the infectious seropositive HCWs required hospitalization. T-SPOT value was 85.0 ± 84.2 SFU/10 6 cells before the third vaccination, which increased to 219.4 ± 230.4 SFU/10 6 cells immediately after, but attenuated later (to 111.1 ± 133.6 SFU/10 6 cells). Poor counts (< 40 SFU/10 6 cells) were present in 34.8% and 38.5% of HCWs before and after the third vaccination, respectively. Our findings provide insights into humoral and cellular immune responses to repeated COVID-19 vaccinations. COVID-19 vaccination was effective in protecting HCWs from serious illness during the original Wuhan-1, Alpha, Delta and also ongoing Omicron-predominance periods. However, repeated vaccinations using current vaccine versions may not induce sufficient cellular immunity in all HCWs.